2018
DOI: 10.4187/respcare.05762
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Low-Cost Bubble CPAP System Designed for Resource-Limited Settings

Abstract: The low-cost bubble CPAP device evaluated in this study is comparable to a bubble CPAP system used in developed settings. Extensive clinical trials, however, are necessary to confirm its effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Although known for decades, the issue of dead space and risk of rebreathing is sometimes neglected when modifying the original bCPAP design 31–33. Without leakage, the use of long connecting tubing to an interface can lead to rebreathing and respiratory failure due to large dead space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although known for decades, the issue of dead space and risk of rebreathing is sometimes neglected when modifying the original bCPAP design 31–33. Without leakage, the use of long connecting tubing to an interface can lead to rebreathing and respiratory failure due to large dead space.…”
Section: Discussionmentioning
confidence: 99%
“…Without leakage, the use of long connecting tubing to an interface can lead to rebreathing and respiratory failure due to large dead space. At least two systems were identified that had neglected the issue of large dead space in their design 31–33…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1B shows real-time recordings of the pressures achieved at the nasal prongs for CPAP settings of 6 and 10 cm H 2 O when the simulated newborn was breathing at 55 breaths/min with a VT of 20 ml. Nasal pressures were stable when compared with other reported bubble CPAP devices (10,11), in terms of both noise induced by bubbling and fluctuations caused by breathing oscillations. Consistent results emerged when breathing of a 10-kg body weight infant (35 breaths/min, 100 ml VT) was simulated through nasal prongs of the corresponding size.…”
Section: Philanthropic Donation Of Conventional Devices This Optionmentioning
confidence: 69%
“…Consistent results emerged when breathing of a 10-kg body weight infant (35 breaths/min, 100 ml VT) was simulated through nasal prongs of the corresponding size. It is important to note that our setting included heated humidification, which was not included in other reports (10,11), because it could be relevant particularly among premature and full-term infants. However, depending on the specific application, this component can be eliminated.…”
Section: Philanthropic Donation Of Conventional Devices This Optionmentioning
confidence: 99%
“…The effectiveness of various bNCPAP devices in reducing neonatal respiratory failure, need for surfactant, mechanical ventilation, and mortality has been evaluated by heterogeneous studies in both developed and developing countries [ 11 , 32 , 34 – 36 ]. In fact, low-cost bNCPAP devices may be comparable in performance to standard bNCPAP systems used in the developed world [ 13 , 36 – 38 ], although some relatively inexpensive bNCPAP devices designed for resource-limited settings are of high resistance, low pressure stability, and impose increased work of breathing [ 39 ].…”
Section: Effectiveness Of Low-cost Bncpapmentioning
confidence: 99%